Simultaneous Detection and Estimation of Catechol, Hydroquinone, and Resorcinol in Binary and Ternary Mixtures Using Electrochemical Techniques - Md. Uzzal Hossain; Md. Toufiqur Rahman; Md. Qamrul Ehsan (International Journal of Analytical Chemistry)
Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were performed with a glassy carbon electrode (GCE) modified with polyglutamic acid (PGA) on the three dihydroxybenzene isomers, catechol (CT), hydroquinone (HQ), and resorcinol (RS). At bare GCE, these isomers exhibited voltammograms with highly overlapped redox peaks that impeded their simultaneous detection in binary and ternary mixtures. On the contrary, at PGA modified GCE binary and ternary mixtures of the dihydroxybenzene isomers showed well-resolved redox peaks in both CV and DPV experiments. This resolving ability of PGA modified GCE proves its potential to be exploited as an electrochemical sensor for the simultaneous detection of these isomers.